Blue and fin whales observed on a seafloor array in the Northeast Pacific - McDonald, Mark A.; Hildebrand, John A; Webb, Spahr C. (eScholarship, University of California, 1995)
Calling blue and fin whales have been tracked using relative travel times and amplitudes from both direct and multipath arrivals to a seafloor array of seismometers. Calls of three fin whales swimming in the same general direction, but several kilometers apart, are believed to represent communication between the whales because of signature differences in call character, an alternating call pattern, and coordination of call and respiration times. Whale call tracks, call patterns, call character, and swimming speeds were examined during periods with and without the presence of noise. Noise sources included airguns, when the whales were subject to sound levels of up to 143 dB P-P (peak-to-peak) re: 1 µPa over the 10 to 60-Hz band, and transits of merchant ships, when the whales received continuous levels up to 106 dB rms re: 1 µPa over the 10 to 60-Hz band (115 dB P-P). Whale responses associated with these noises remain arguable.